2022
DOI: 10.3390/ijerph191710545
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Grief Symptoms among Suicide-Loss Survivors: The Contribution of Intrapersonal and Interpersonal Characteristics

Abstract: Background: Suicide-loss survivors (SLSs) are a population with unique characteristics that place them at increased risk for developing grief complications and painful feelings of guilt that may impact their supportive social environment. However, no studies to date have examined the role of intrapersonal and interpersonal variables that may contribute to prolonged grief symptoms (PGS) as outlined by the new DSM-5 criteria. The present study aimed to extend knowledge regarding the role of interpersonal variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Moreover, self-disclosure can carry the benefit of decreasing SLSs’ psychological difficulties, such as depression and suicide ideation (Van Orden et al, 2010 ). In recent studies, ii was found that experiences such as belongingness serve as a factor that diminishes CG levels (Levi-Belz & Aisenberg, 2021 ) and depression (Levi-Belz & Ben-Yaish, 2022 ) in the aftermath of suicide loss. Thus, grief and depression levels may also be related to the nature of SLSs’ interpersonal engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, self-disclosure can carry the benefit of decreasing SLSs’ psychological difficulties, such as depression and suicide ideation (Van Orden et al, 2010 ). In recent studies, ii was found that experiences such as belongingness serve as a factor that diminishes CG levels (Levi-Belz & Aisenberg, 2021 ) and depression (Levi-Belz & Ben-Yaish, 2022 ) in the aftermath of suicide loss. Thus, grief and depression levels may also be related to the nature of SLSs’ interpersonal engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies (e.g. Levi-Belz & Ben-Yaish, 2022 ; Shu-Liang et al, 2020 ), self-disclosure was found to be related to higher levels of perceived social support and belongingness, which have been recognised as factors that may contribute to SLSs’ recovery from their suicide loss (Levi-Belz & Aisenberg, 2021 ). Thus, self-disclosing emotional aspects of traumatic events to others may facilitate changes in loneliness and social support, as well as craft new ways of thinking about oneself and the suicide event (Levi-Belz, 2015 ), thus easing the harsh feelings of shame and its ramifications (Levi-Belz & Gilo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such relationships may amplify the oppressive experience of blame and shame, which characterize many SLSs (e.g., Refs. [ 5 , 47 ]) and hinder their recovery from depressive symptoms. The more acute grieving process of SLSs with high TB [ 10 ] may also play a role in the association between low social relationships and depression, promoting lasting symptoms of depression for the high TB group.…”
Section: Discussionmentioning
confidence: 99%
“…The more acute grieving process of SLSs with high TB [ 10 ] may also play a role in the association between low social relationships and depression, promoting lasting symptoms of depression for the high TB group. On the other hand, a higher sense of belongingness, viewed as one of the fundamental human psychological needs [ 48 ], may function as a buffer against the stigma and shame experienced by SLSs [ 5 , 47 ] and, as a result, shield SLSs from mental pain and even depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that suicide-loss survivors present higher levels of depression, and suicidal ideation and behavior [ 6 , 7 ] than other bereaved individuals. Moreover, those bereaved by suicide can experience adverse grief reactions such as prolonged grief disorder symptoms [ 8 , 9 ] which can persist even several years following the loss.…”
mentioning
confidence: 99%